Sexual Traumatic Event Exposure, Posttraumatic Stress Symptomatology, and Alcohol Misuse Among Women: A Critical Review of the Empirical Literature. Issue 1 (24th October 2016) - Langdon, Kirsten J.; Rubin, Amy; Brief, Deborah J.; Enggasser, Justin L.; Roy, Monica; Solhan, Marika; Helmuth, Eric; Rosenbloom, David; Keane, Terence M.
Abstract : The current review summarizes and critically evaluates the existing literature to shed light on two key questions: (a) the impact of trauma exposure on alcohol use (and vice versa; the impact of alcohol use on risk for trauma exposure) in women, and (b) the nature of PTSD–alcohol misuse comorbidity in women. The secondary aim was to explore moderators or mechanisms of action. Findings suggest that sexual trauma may be especially relevant to alcohol misuse in women. Cross‐sectional data generally support PTSD–alcohol misuse associations; however, findings from prospective studies are mixed. Significantly less is known about moderators/mediators of these relations, with the majority of work focused on emotional and motivational processes. Limitations, future directions, and clinical implications are discussed.